2018
DOI: 10.1111/petr.13129
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized, controlled trial of eculizumab to prevent ischemia‐reperfusion injury in pediatric kidney transplantation

Abstract: Ischemia-reperfusion injury has multiple effects on a transplanted allograft, including delayed or impaired graft function, compromised long-term survival, and an association with an increased incidence of rejection. Eculizumab, a monoclonal antibody blocking terminal complement activation, has been postulated to be an effective agent in the prevention or amelioration of IRI. We performed a single-center prospective, randomized controlled trial involving 57 pediatric kidney transplant recipients between 2012 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 19 publications
0
40
1
1
Order By: Relevance
“…The authors reported that a single pretransplant Ecu dose was associated with better early graft function and fewer chronic histological changes on long-term protocol biopsies. 16 The reason for the discrepancy between the convincing scientific evidence regarding the causal involvement of complement in the IR injury and lack of efficacy of Ecu in our current study and the PROTECT Study is unknown, but may relate to specificity of the Ecu's complement inhibitory function. 9,17,18 Ecu inhibits the C5 con- Alternatively, as complement activation initiates within the donor kidney coincident with donor death, 10,11 it is conceivable that initiating complement inhibition earlier than what was done in this study, eg, in the donor or during cold storage, could be efficacious.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The authors reported that a single pretransplant Ecu dose was associated with better early graft function and fewer chronic histological changes on long-term protocol biopsies. 16 The reason for the discrepancy between the convincing scientific evidence regarding the causal involvement of complement in the IR injury and lack of efficacy of Ecu in our current study and the PROTECT Study is unknown, but may relate to specificity of the Ecu's complement inhibitory function. 9,17,18 Ecu inhibits the C5 con- Alternatively, as complement activation initiates within the donor kidney coincident with donor death, 10,11 it is conceivable that initiating complement inhibition earlier than what was done in this study, eg, in the donor or during cold storage, could be efficacious.…”
Section: Discussioncontrasting
confidence: 65%
“…16 Of note, in this latter study 68% were living donor kidney recipients. The inability of Ecu to improve early transplant outcome in our current study and the PROTECT study are in contrast to a single center, not-blinded, randomized, placebo controlled trial involving 57 pediatric kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Kabaak et al chose an immunosuppressive protocol with induction therapy with two doses of alemtuzumab at 1 mg/kg, a monoclonal antibody that binds to CD52, a protein present on the surface of mature lymphocytes, which is commonly used in the pediatric renal transplant program in Madison, WI . This was combined with tacrolimus (trough levels of tacrolimus were adjusted to 8‐12 ng/mL for the first 10 days and 2‐8 ng/mL thereafter) and MMF (fixed dose, no pharmacokinetic monitoring).…”
Section: The Study By Kaabak Et Almentioning
confidence: 99%
“…First of all, Michael Kaabak et al clearly chose an innovative approach. While underpowered to demonstrate a long‐term benefit, the significantly better early function resulted in a trend toward a better eGFR at 3 years and significantly better histopathology.…”
Section: So What Can We Learn From This Trial?mentioning
confidence: 99%